PENGARUH MODEL PEMBELAJARAN BEYOND CENTERS AND CIRCLE TIME TERHADAP KREATIVITAS ANAK DI TK MUJAHIDIN PONTIANAK - Zurniasti, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The research was distributed by the learning model is an important factor affect in growth in the learning process. One of them is creativity. Researcher conducted observations on A group of TK Mujahidin 1, researcher saw a childrens creative, but on the other hand there are also children who are less creative, despite being given the same learning model of treatment. Therefore, Researcher want to see if the model beyond learning cemters and circle time applied by the effect on children?s creativity before using the model of learning Beyond Centers and Circle Time, after three months and after six months. Based on the analysis of data obtained FO of 748.788 and Ftable to test the two parties on the significance level ? = 5% and df = 2 numerator denominator = 333, with interpolation done after obtained Ftable of 3.02. Thus, FO > Ftable, then the zero hypothesis was rejected. That is, there is a learning model of influence Beyond Centers and Cirle Time against A group of children creativity Mujahidin 1 South Pontianak. The conclusion is a model of learning Beyond Centers and Circle Time effect significantly to children creativity. Keywords: Model Of Learning Beyond Centers And Circle Time, Creativity